2023
DOI: 10.1086/725391
|View full text |Cite
|
Sign up to set email alerts
|

Fire Responses Shape Plant Communities in a Minimal Model for Fire Ecosystems across the World

Abstract: Across plant communities worldwide, fire regimes reflect a combination of climatic factors and plant characteristics. To shed new light on the complex relationships between plant characteristics and fire regimes, we developed a new conceptual, mechanistic model that includes plant competition, stochastic fires, and fire-vegetation feedback. Considering a single standing plant functional type, we observed that highly flammable and slowly colonizing plants can persist only when they have a strong fire response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 159 publications
0
1
0
Order By: Relevance
“…A variety of non‐spatial theoretical models that make reasonable ecological assumptions have demonstrated that savanna and forest can be AES (e.g. van Langevelde et al ., 2003; Scheiter & Higgins, 2007; Accatino et al ., 2010; Baudena et al ., 2010; Staver et al ., 2011a; Staver & Levin, 2012; Goel et al ., 2020; Djeumen et al ., 2021; Magnani et al ., 2023). Such models demonstrate that for a single set of parameters that the ecosystem states forest or savanna can emerge as stable states and which emerges depends on the initial conditions (Fig.…”
Section: Theoretical Evidence For Savanna‐forest Aesmentioning
confidence: 99%
“…A variety of non‐spatial theoretical models that make reasonable ecological assumptions have demonstrated that savanna and forest can be AES (e.g. van Langevelde et al ., 2003; Scheiter & Higgins, 2007; Accatino et al ., 2010; Baudena et al ., 2010; Staver et al ., 2011a; Staver & Levin, 2012; Goel et al ., 2020; Djeumen et al ., 2021; Magnani et al ., 2023). Such models demonstrate that for a single set of parameters that the ecosystem states forest or savanna can emerge as stable states and which emerges depends on the initial conditions (Fig.…”
Section: Theoretical Evidence For Savanna‐forest Aesmentioning
confidence: 99%